Naturalistyczna muzykologia systematyczna wobec poglądów Meyera na emocje i znaczenie w muzyce - Podlipniak, Piotr (Res Facta Nova, 2020)
Leonard B. Meyer’s book Emotion and Meaning in Music was published more than half a century ago. It still provides inspiration for musicologists with various specialisms to undertake research aimed at understanding the intriguing link between music and emotions and the relationship between musical structure and meaning. Since the publication of this outstanding volume we have seen extraordinarily dynamic development of the musicological disciplines constituting that part of systematic musicology which is based on the premises of naturalism. The article focuses on those selected research areas of thisbranch of musicology where the influence of the ideas first presented in the above volume is particularly significant. The most important of Meyer’s postulates in naturalistically oriented systematic musicology that continue to be discussed include: the key role of expectation in shaping our emotional reactions to the musical passages we hear and the inner musical character of the affective meanings created in this way. The main challenges faced by Meyer’s postulates during the recent decades are examined, and the solutions to them proposed within the framework of naturalistically oriented thinking about music.